Small Bowel Obstruction in Postpartum Vaginal Delivery due to Prior Abdominal Adhesions Case Report - Liubin Yang; Lydia Kao (Hindawi Limited, 2023)
Intestinal obstruction rarely occurs after uncomplicated vaginal deliveries. Here, we present a case of a multiparous woman with a history of prior appendectomy presenting with generalized, nonspecific abdominal pain that was out of proportion to exam findings. Initial abdominal X-ray was nonspecific, and subsequent computed tomography (CT) abdomen showed closed small bowel obstruction requiring surgical repair. We present a case of intestinal obstruction occurring within 24 hours of uncomplicated vaginal delivery with a risk factor of a prior appendectomy surgery and the use of CT abdomen and pelvis to expedite diagnose.